EFFECTS OF FAMILY HEALTH ON ADOLESCENT STUDENTS IN CHIAPAS, MEXICO - Espinosa, Lucio Abdiel Olmedo; Ordoñez, Nora Natalia Pérez (Seven Editora, 2025)
The present study aimed to determine whether family health levels predict the risk of adolescent problems and symptoms of depression in high school students in Chiapas, Mexico. This was a quantitative, cross-sectional, descriptive, explanatory, and comparative research study, in which 150 students (aged 14 to 19 years) selected through simple random probability sampling participated. The instruments used were the Family Health Status Self-Perception Questionnaire v2 (α = .961), the POSIT (α = .965), and the Beck Depression Inventory (α = .966), which allowed measuring the dimensions of family health, risk of adolescent problems, and symptoms of depression, respectively. The study found that levels of family health significantly explain the risk of adolescent problems and depressive symptoms, suggesting that family health has an important influence on students' psychosocial well-being. This finding highlights the importance of strengthening family health factors as a preventive measure in the educational context.DOI: https://doi.org/10.56238/sevened2025.018-015